Arterial hypertension and cardiovascular risk factors in student population - A. A. El’garov; L. V. El’garova (Кардиоваскулярная терапия и профилактика, 1970)
Aim. То study he prevalence of arterial hypertension (AH) and other cardiovascular disease (CVD) risk factors (RF) in student population. Material and metliods. In total, 508 students of Kabardino-Balkar State University (150 men, 358 women) were examined clinically and epidemiologically (mean age 19,5±1,5 years). In sub-samples, anonymous questionnaire survey was performed, to investigate actual smoking prevalence, and to assess personal and reactive anxiety levels by Spielberger-Khanin method. Results. Mean levels of systolic and diastolic blood pressure (SBP, DBP), anthropometry parameters, and lipid profile were assessed. CVD RF were widely prevalent in the student population. In males, AH, overweight (OW), hypercholesterolemia (HCH), and smoking were diagnosed significantly more often than in females. Regardless of gender, every second student consumed alcohol. Most participants demonstrated high levels of personal and reactive anxiety. Conclusion. Adverse epidemiological situation with AH and other CVD RF was observed in students. This points to young persons' vulnerability, and the need for active implementation of preventive measures.